Alteration of pro-carcinogenic gut microbiota is associated with clear cell renal cell carcinoma tumorigenesis - Yang, Bo-Yu; Zhao, Fang-Zhou; Li, Xuan-Hao; Zhao, Mei-Shan; Lv, Jing-Cheng; Shi, Ming-Jun; Li, Jun; Zhou, Zhi-Yuan; Wang, Jing-Jing; Song, Jian (Frontiers in Microbiology, 2023)
Increasing evidence suggests that gut microbiota is involved in the occurrence and progression of urinary system diseases such as clear cell renal cell carcinoma (ccRCC). However, the mechanism of how alteration of gut metagenome promotes ccRCC remains unclear. Here we aim to elucidate the association of specific gut bacteria and their metabolites with ccRCC. In a pilot case-control study among 30 ccRCC patients and 30 healthy controls, 16S ribosomal RNA (rRNA) gene sequencing were analyzed from fecal samples collected prior to surgery or hospitalization. Alpha diversity and beta diversity analysis of the gut microbiota were performed, and differential taxa were identified by multivariate statistics. Meanwhile, serum metabolism was measured by UHPLC-MS, and differential genes were identified based on the TCGA database. Random Forests revealed the relative abundances of 20 species differed significantly between the RCC group and the Control group, among which 9 species, such as Desulfovibrionaceae, were enriched in the RCC group, and 11 species, such as four kinds of Lactobacillus, were less abundant. Concomitantly, serum level of taurine, which was considered to be consumed by Desulfovibrionaceae and released by Lactobacillus, has decreased in the RCC group. In addition, macrophage-related genes such as Gabbr1 was upregulated in ccRCC patients from our results.